Prevalence of Transfusion Transmitted Infection among Blood Donors at Medical University in Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Blood transfusion is associated with a number of complications. Transfusion transmitted infections (TTI) are one of the major health problem in Bangladesh.Objective: The objective of the present study was to assess the status of transfusion transmitted infections among the apparently healthy donors.Methodology: This study we carried out among 12,294 blood donors from September 2009 to March 2010 at Department of Transfusion Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. All the samples were screened for hepatitis B surface antigen (HBsAg), hepatitis C virus (HCV), human immunodeficiency virus (HIV) 1 and 2, venereal disease research laboratory test (VDRL) and malaria to see the prevalence of TTI.Results: Prevalence of HBV, HCV, HIV, and syphilis were 0.009, 0.0004, 0.0001 and 0.0001% respectively. No blood donor tested showed positivity for malarial parasite.Conclusion: Mandatory screening of donated blood and use of sensitive screening test should be done to reduce TTI in Bangladesh.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 11-13